STEROIDS V 1 THE SYNTHESIS OF ADRENAL CORTICOSTEROIDS AND ANALOGS FROM ALL OPREGNAN 3 20 ONE - ROSENKRANZ, G; PATAKI, J; KAUFMANN, ST; DJERASSI, CARL; BERLIN, J (LABORATORIOS SYNTEX, CD. MEXICO, DF, MEX, 1950)
The synthesis of a number of 11-desoxy-17Î±,-hydroxy-20-ketosteroids has been described. Allopregnan-3Î²-ol-20-one 3-acetate (V), a readily available starting material from plant sources, has been converted through Reichstein's substance L (VI) to allopre
J VAC SCI TECHNOL
Keywords: STEROIDS, SYNTHESIS, ADRENAL CORTICOSTEROIDS, ANALOGS, OPREGNAN 3 20 ONE; QUIMICA; QUIMICA ORGANICA; HIDROCARBUROS AROMATICOS